The role of neurectomy in the management of spasticity of the upper limb. Issue 11 (27th November 2017) - Mikalef, Petros; Power, Dominic
Abstract : Neurectomy is one of the treatments available to the surgeon treating patients with spasticity of the upper limb. Its popularity has increased in recent years. Accurate knowledge of the anatomical variations of the terminal branches to the muscles is required in order to achieve a successful outcome. Although the anatomy has been thoroughly studied, there are still controversies regarding the percentage of the nerve to be resected for a successful result, and also regarding the terminology that has been used in the literature to describe the procedure. The literature for neurectomies for the upper limb is reviewed and an agreement regarding terminology is proposed. Cite this article: EFORT Open Rev 2017;2:469-473. DOI: 10.1302/2058-5241.2.160074